The differential diagnostic values of cytokine levels in pleural effusions - Akarsu, S; Kurt, ANC; Dogan, Y; Yilmaz, E; Godekmerdan, A; Aygun, AD (Wiley, 2005)
The aim is to examine whether the changes in pleural fluid interleukin (IL)-1 beta, IL-2, IL-6, and IL-8 levels were significant in differential diagnosis of childhood pleural effusions. IL-1 beta, IL-2, IL-6, and IL-8 levels in pleural fluids of all 36 patients were measured. The levels of IL-1 beta, IL-2, IL-6, and IL-8 in pleural fluids were statistically significantly higher in the transudate group compared with those of the exudate group. The levels of IL-1 beta, IL-6, and IL-8 were also found to be statistically significantly higher in the empyema group compared with both the parapneumonic and the tuberculous pleural effusion groups. The levels of IL-2 and IL-6 were detected to be statistically significantly higher in the tuberculous pleural effusion group in comparison with those of the parapneumonic effusion group. The results showed that pleural fluids IL-1 beta, 1L-2, IL-6, and IL-8 could be used in pleural fluids exudate and transudate distinction.
Keywords: Tumor-Necrosis-Factor; Biochemical Parameters; Empyema; Interleukin-8; Children; Fluids; Cells; Il-8